(untitled) - Mohanty, Hrushikesha; Bhuyan, Prachet (Springer (India) Private Limited, 2015)
Ebook from Proquest
Keywords: Computers -- Databases -- Data Mining; Computer -- System Administration -- Storage & Retrieval; Tin học -- Dữ liệu máy tính